Effect of operators' experience and cement space on the marginal fit of an in-office digitally produced monolithic ceramic crown system - Baig, Mirza Rustum; Gonzalez, Maria Angela G.; Abu Kasim, Noor Hayaty; Abu Kassim, Noor Lide; Farook, Mohideen Salihu (Quintessence Publishing Co. Inc., 2016)
Objectives: To investigate the marginal accuracy of Cerec three-dimensional (3D) all-ceramic crowns, in terms of gap and overhang, and to analyze the "operators' experience" and "cement space" effects on the marginal fit. Method and Materials: Thirty virtual models were obtained from a metal master die by scanning by three different operators: operator 1 (novice), operator 2 (beginner), and operator 3 (expert) (n = 10). These were further divided into two subgroups of five each, based on the cement space settings: 10 μm and 20 μm. Monolithic ceramic crowns (n = 10) were designed and milled for each virtual model and subjected to marginal gap and overhang evaluation at six designated margin locations. The influence of operators' experience and cement space on the marginal fit of the crowns was assessed by performing Box tests and MANOVA (multiple analysis of variance) (α = .05). Kruskal Wallis test was also used to analyze the interactions between the operators' experience and the cement space. Results: The overall mean ± SD marginal gaps and overhangs for the Cerec 3D crowns, were 154 ± 56 μm and 74 ± 74 μm for novice, 158 ± 53 μm and 86 ± 66 μm for beginner, and 155 ± 52 μm and 47 ± 76 μm for expert, respectively. The MANOVA and Kruskal Wallis tests found no significant differences (P > .05) between the operators, in terms of gap and overhang, for all cement settings. Conclusion: The operator experience did not seem to influence the marginal accuracy of Cerec 3D fabricated crowns.